Integrating patient-centered learning strengthens concept mastery, problem-solving, and patient awareness in undergraduate immunology - Cleveland, Dawn W.; Sletten, Sarah (Frontiers in Education, 2025)
BackgroundImmunology is a complex subject that students and instructors often find challenging. Active learning (AL) strategies, particularly patient-centered learning (PCL) within a team-based learning (TBL) framework, may enhance student engagement and conceptual understanding while fostering clinical reasoning and empathy development.MethodsThis study examines the effectiveness of PCL case studies in an undergraduate immunology course at a public R1 university. Students engaged in multi-day case studies, analyzing patient histories, symptoms, diagnostic results, and treatment plans while integrating foundational immunology concepts. Data were collected through end-of-course evaluations, including a Likert-scale item (quantitative) and two open-ended questions (qualitative).ResultsStudents reported high agreement (mean = 4.72, SD = 0.74) that PCL enhanced their understanding of immunology. Thematic analysis of open-ended responses revealed six key learning outcomes, including real-world application, critical thinking, preparation for medical careers, and patient connection. Additionally, students identified diagnostic reasoning, problem-solving, and teamwork as skills gained. However, empathy was not explicitly mentioned, suggesting a need for more structured reflection-based activities in undergraduate coursework.ConclusionPCL improves concept mastery, clinical reasoning, and diagnostic skills in undergraduate immunology education. However, while case studies introduced patient-centered elements, students did not self-report increased empathy. Future course designs should incorporate intentional scaffolding of empathy development, such as guided reflections and interprofessional discussions, to better integrate scientific knowledge with humanistic awareness.